Significance Of The Speaking Skill In The Workplace And Academic Contexts - Dr. prema S; Aruna Arputhamalar (Cita konsultindo, 2022)
The present technologically advanced global business has brought in the need for effective communication. A universal language has become mandatory to unite all forms of communication like listening, speaking, reading, and writing. The English language has taken this role of eminence, wherein people of various nations and creeds use the language to communicate effectively. Of the four language skills, the speaking skill has taken a predominant role in effective corporate communication. Thereby this study aims to understand the importance of speaking skill in academic and workplace contexts. A survey questionnaire was circulated to 128 engineering students to understand their perception on the speaking skill. The survey shows that the students perceived their speaking skill to be – good.